Chapter The Torre del Marzocco and the widening of the entry channel to the industrial port of Livorno - Pribaz, Enrico (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Torre is an ancient watchtower, (15th century), and is subject to Italian laws for the protection of the historical and cultural heritage. Located in the port of Livorno the Torre del Marzocco symbolizes the past rooted in port activities and its traffic. This contribution presents a project of NTSNA to redevelop and renovate ancient marine landscape of Marzocco Tower. The project aims to widen the entry channel to Livorno port, as a safety measure towards the secure access of the great ships of new generation to the industrial area of Livorno's port.